Exercise and stretch therapy in the complex treatment of Charcot-Marie-Tooth hereditary neuropathy - S. Goncharova (Спортивная медицина: наука и практика, 2020)
Despite the success of multicentre molecular genetic studies in the field of hereditary neuromuscular diseases, the problem of complex treatment of this pathology remains relevant to this day. The main goal of therapy is to adapt patients to the disease, slowing progression and improving quality of life by increasing daily physical activity. This article describes features of clinical picture of Charcot-Marie-Tooth hereditary neuropathy and approaches to its rehabilitation. Authors show that the basis of physical rehabilitation is therapeutic physical culture, which should be used already at the preclinical stage of the disease development in order to reduce the rate of its progression. It is important that the process of rehabilitation of patients with Charcot-Marie-Toot hereditary neuropathy should continue throughout their life.